Edukasi dan Implementasi Layanan Mediasi dalam Mengatasi Pelanggaran Tata Tertib Siswa di SMP Muhammadiyah 57 Medan - Imron Bima Saputra; Muhammad Luthfie Ramadhani; Nursyahrul Ritonga; Roslaeni Roslaeni; Indra Syah Putra; Agus Salim (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2026)
This research aims to analyze the general picture of student disciplinary violations, implementation of education and understanding of rules, the process of implementing mediation services, and the effectiveness of mediation services in resolving violations.This community service (PkM) program involves determining the subject or target audience, implementing the activity, and collecting and analyzing data. This section explains how the team identifies problems, implements solutions, and measures the program's success in the field. Data collection methods include observation, interviews, and document review. Student disciplinary violations at SMP Muhammadiyah 57 Medan are still dominated by minor violations, indicating that some students have not yet optimally internalized the value of discipline. Efforts to educate and understand the rules have been implemented through socialization of disciplinary rules, classical guidance, coaching by guidance counselors, homeroom teachers, and subject teachers, thereby increasing students' understanding of the importance of discipline and responsibility. The implementation of mediation services is carried out systematically through problem identification, mediation processes, education, and follow-up, so that they not only function to resolve conflicts but also shape character, improve communication skills, and raise students' awareness to comply with school rules. Mediation services have proven effective in reducing disciplinary violations, improving interpersonal relationships, and strengthening a culture of discipline and Islamic character within SMP Muhammadiyah 57 Medan through collaboration between guidance counselors, the principal, homeroom teachers, teachers, and parents.